Comparative response of fennel, ajwain, and anise in terms of osmolytes accumulation, ion imbalance, photosynthetic and growth functions under salinity - Javad Nouripour-Sisakht; Parviz Ehsanzadeh; Mohammad H. Ehtemam (Scientific Reports)
Abstract The increasing trend of salinization of agricultural lands represents a great threat to the growth of major crops. Hence, shedding light on the salt-tolerance capabilities of three environment-resilient medicinal species from the Apiaceae, i.e. fennel, ajwain, and anise as alternative crops was aimed at. Two genotypes from each of the three medicinal species were exposed to a wide range of water salinities, including 0 (control), 40, 80, and 120 mM NaCl and comparative changes in the leaf photosynthetic pigments, osmoticums, antioxidative enzymes, ionic homeostasis, essential oil, and plant growth were assessed. Even though certain genotype- and species-specificities were observed in the salt-induced modifications of these physiological attributes, decreasing in growth, plant dry mass, root volume, relative water content, and K+ concentration concomitant to increasing in the catalase, ascorbate peroxidase, and guaiacol peroxidase activities, malondialdehyde, total soluble carbohydrates, proline and Na+ concentrations, Na+/K+, and essential oil were common to the examined species and genotypes. The K+ concentration of the stressed plants of anise genotypes was smaller, giving shape to a greater Na+/K+ than those of fennel and ajwain. Unlike anise, fennel and ajwain genotypes retained and/or increased the chlorophyll and carotenoids concentrations when exposed to 120 mM NaCl. The greater salt-induced increases in the catalase, ascorbate peroxidase, and guaiacol peroxidase activities along with the less-heightened Na+/K+ were concomitant to the smaller depressions in the total plant dry mass and root volume of the fennel and ajwain genotypes, portraying these species more resilient to saline water, compared to anise.